2014
DOI: 10.1016/s1995-7645(14)60246-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheat grass powder on aluminum induced Alzheimer's disease in Wistar rats

Abstract: The present study clearly demonstrated the beneficial effects of wheat grass that shows good antioxidant properties, and this remarkable effect of wheat grass may act as a key to treat Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Antioxidants and free radical scavengers such as selenium, melatonin, boric acid and vitamin C have been employed experimentally to ameliorate the deleterious effects of free radicals produced as a result of Al intoxication (Omar et al, 2003;Abubakar et al, 2004;Fyiad, 2007;Turkez et al, 2011). Other researchers have used plant extracts of fenugreek seed, grape seed, ginger, wheat grass powder, black tea, Allium cepa, Caesalpinia crista, Arthrophytum (Hammada scoparia), Moringa oleifera and Celastrus paniculatus to ameliorate the toxicosis caused by Al exposure (Khattab et al, 2010;Hasseeb et al, 2011;Osman et al, 2012;Belaïd-Nouira et al, 2013;Sumathi et al, 2013;Bitra et al, 2014;Osama et al, 2014;Mathiyazahan et al, 2015;Singh and Goel, 2015;Taїr et al, 2016;Ravi et al, 2018). The neuronal death in the hippocampus of the brain associated with neurodegeneration in rats caused by Al exposure was attenuated by quercetin (Sharma et al, 2016).…”
Section: Diagnosis and Treatment Of Aluminium Intoxicationmentioning
confidence: 99%
“…Antioxidants and free radical scavengers such as selenium, melatonin, boric acid and vitamin C have been employed experimentally to ameliorate the deleterious effects of free radicals produced as a result of Al intoxication (Omar et al, 2003;Abubakar et al, 2004;Fyiad, 2007;Turkez et al, 2011). Other researchers have used plant extracts of fenugreek seed, grape seed, ginger, wheat grass powder, black tea, Allium cepa, Caesalpinia crista, Arthrophytum (Hammada scoparia), Moringa oleifera and Celastrus paniculatus to ameliorate the toxicosis caused by Al exposure (Khattab et al, 2010;Hasseeb et al, 2011;Osman et al, 2012;Belaïd-Nouira et al, 2013;Sumathi et al, 2013;Bitra et al, 2014;Osama et al, 2014;Mathiyazahan et al, 2015;Singh and Goel, 2015;Taїr et al, 2016;Ravi et al, 2018). The neuronal death in the hippocampus of the brain associated with neurodegeneration in rats caused by Al exposure was attenuated by quercetin (Sharma et al, 2016).…”
Section: Diagnosis and Treatment Of Aluminium Intoxicationmentioning
confidence: 99%
“…The result is consistent with previous works on AlCl 3 -induced AD. [47,48,51,[52][53][54] Earlier studies reported that the accumulation of Aβ (as revealed in Figure 6A) has a great contribution to cognitive impairment in both human and animal AD. [55][56][57] In addition, evidence supports the beneficial impact of insulin signaling on memory and learning; [10][11][12] biotin.…”
Section: F I G U R Ementioning
confidence: 99%
“…It is also documented that Rosmarinic acid had two cathecol moieties, which consequently induces morphological and signature changes in the secondary structure of tauprotein once it is interacted with, thus, preventing aggregation and β-sheets assembly and also reducing fibril progression (Cornejo et al, 2015). Both RO and BM effects on all afore-mentioned biochemical markers and histopathological results were comparable to Donazil®™, a standard selective inhibitor of brain cholinesterase commonly used in AD management (Bitra et al, 2014;Nayak and Chatterjee, 2001).…”
Section: E Ffe C T O Fmentioning
confidence: 61%
“…Aluminum chloride (AlCl3) was purchased from Sigma-Aldrich Chemicals Co, Egypt, dissolved in saline 0.9% and injected intraperitonealy (I.P) at dose 4.2 mg/kg/day for 28 days according to methodology of Bitra et al (2014) and Nayak and Chatterjee (2001). Ethanol (analytical grade) was purchased from El Gomhoreya Co., Egypt.…”
Section: Chemicals and Drugsmentioning
confidence: 99%